2021
DOI: 10.3389/fgene.2021.695699
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of mRNA- and miRNA-Seq in the Ovary of Rare Minnow Gobiocypris rarus in Response to 17α-Methyltestosterone

Abstract: 17α-Methyltestosterone (MT) is a synthetic androgen. The objective of this study was to explore the effects of exogenous MT on the growth and gonadal development of female rare minnow Gobiocypris rarus. Female G. rarus groups were exposed to 25–100 ng/L of MT for 7 days. After exposure for 7 days, the total weight and body length were significantly decreased in the 50-ng/L MT groups. The major oocytes in the ovaries of the control group were vitellogenic oocytes (Voc) and cortical alveolus stage oocytes (Coc).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Studies have shown that sf1 plays crucial roles in slider turtle sex differentiation and determination [ 43 ] and is an essential regulator of gonad development in Nile tilapia [ 44 ]. Foxo3 has been shown to be involved in ovarian development in the Gobiocypris rarus [ 45 ], and it upregulates cyp19a1a during vitellogenesis in the orange-spotted grouper [ 46 ]. Gata4 is not only required for gonad differentiation in tilapia but also important to gonad development and maturation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that sf1 plays crucial roles in slider turtle sex differentiation and determination [ 43 ] and is an essential regulator of gonad development in Nile tilapia [ 44 ]. Foxo3 has been shown to be involved in ovarian development in the Gobiocypris rarus [ 45 ], and it upregulates cyp19a1a during vitellogenesis in the orange-spotted grouper [ 46 ]. Gata4 is not only required for gonad differentiation in tilapia but also important to gonad development and maturation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…MFAP4 has also been implicated in other processes. It was reported among the differentially expressed genes in the gonads of the female rare minnow after stimulation with synthetic androgen 17α-methyltestosterone [121], implying its potential involvement in ovarian development. In another RNAseq study, mfap4 was downregulated in the carpgoldfish transparent mutants relative to WT fish, with an accompanying upregulation of mfap4-targeting miRNA-146a, suggesting its association to pigmentation [122].…”
Section: Mfap4 and Its Role In Teleost Fishmentioning
confidence: 99%